2009
DOI: 10.1016/j.conb.2009.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of myelinated axons in zebrafish

Abstract: In the vertebrate nervous system, the myelin sheath allows for rapid and efficient conduction of action potentials along axons. Despite the essential function of myelin, many questions remain unanswered about the mechanisms that govern the development of myelinated axons. The fundamental properties of myelin are widely shared among vertebrates, and the zebrafish has emerged as a powerful system to study myelination in vivo. This review will highlight recent advances from genetic screens in zebrafish, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…That is actually an important issue in the pathogenic mechanism of the disease because myelin cell function overtakes action potential conduction along peripheral axons (Monk and Talbot, 2009). In fact, the control of axoplasmic Ca 2+ and posttranslational modifications of local trafficking proteins are part of trophic support signaling provided by myelinating cells.…”
Section: Discussionmentioning
confidence: 99%
“…That is actually an important issue in the pathogenic mechanism of the disease because myelin cell function overtakes action potential conduction along peripheral axons (Monk and Talbot, 2009). In fact, the control of axoplasmic Ca 2+ and posttranslational modifications of local trafficking proteins are part of trophic support signaling provided by myelinating cells.…”
Section: Discussionmentioning
confidence: 99%
“…The PLLn does not cross the basement membrane in Schwann cell-deficient mutants Sox10 is essential for the development of Schwann cells and other neural crest derivatives . In Schwann cells, ErbB2 and ErbB3 form a heteromeric receptor that is required for glial proliferation, migration and differentiation (Lyons et al, 2005;Monk and Talbot, 2009;Nave and Salzer, 2006). We have previously reported that in mutants lacking Schwann cells, including erbb2 st61 , erbb3 st48 and sox10 (cls t3 ) mutants, the PLLn is aberrantly localized in the epidermis at 3 dpf (Voas et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…That is, most of the critical molecular machinery of myelination is conserved between zebrafish and mammals (Monk and Talbot, 2009). Most important, the zebrafish model allows us to precisely study signaling mechanisms at the onset of myelination.…”
Section: Components Of the Canonical Wnt Signaling Pathway Drive Myelmentioning
confidence: 99%
“…Embryos were heat shocked at 2 dpf, corresponding to the onset of zebrafish myelination, whereby oligodendrocytes and Schwann cells start expressing myelin genes (Brosamle and Halpern, 2002;Lyons et al, 2005). mbp mRNA expression, a widely used marker for the onset of myelination in zebrafish (Monk and Talbot, 2009), was analyzed at 4 or 5 dpf by in situ hybridization at the level of the peripheral lateral line (PLLn), where axons are solely myelinated by Schwann cells.…”
Section: Interaction Between ␤-Catenin and Tcf3 Is Required For Schwamentioning
confidence: 99%